The effects of resisted sled-pulling sprint training on acceleration and maximum speed performance - Zafeiridis, A.; Saraslanidis, P.; Manou, V.; Ioakimidis, P.; Dipla, K.; Kellis, S. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purpose of the present study was to examine the effects of resisted (RS) and un-resisted (US) sprint training programs on acceleration and maximum speed performance. Methods: Twenty-two male students (age 20.1±1.9 y, height 1.78±7 cm, and weight 73±2 kg) completed RS (n=11) or US (n=11) sprint training programs. The RS group followed a sprint-training program with 5 kg sled pulling and the US group followed a similar sprint-training program without sled pulling. The training program consisted of 4¥20 m and 4¥50 m maximal runs, and was applied 3 times/week for 8 weeks. Before and after the training programs the subjects performed a 50 m run and the running velocity of 0-10 m, 10-20 m, 20-40 m and 40-50 m was measured. In addition, stride length and stride frequency were evaluated at the 3rd stride in acceleration phase and between 42-47 m in maximum speed phase. Results: The RS improved running velocity in the run sections 0-10 m and 0-20 m, while in US group the running velocity in all run sections in acceleration phase remained unchanged (p>0.05). In contrast, RS training had no effect on running velocity in maximum speed phase, whereas US improved running velocity in 20-40 m, 40-50 m, and 20-50 m run sections (p<0.05). Stride rate increased only after RS in acceleration phase (+7.1±2.9%; p<0.05), whereas stride length increased only after US in maximum speed phase (+5.5±2.5%; p<0.05). Conclusion: Sprint training with 5 kg sled pulling for 8 weeks improves acceleration performance (0-20), while un-resisted sprint training improves performance in maximum speed phase (20-40) in non-elite athletes. It appears that each phase of sprint run demands a specific training approach.